Observed Loss and Ineffectiveness of Mosquito Larvicides Applied to Catch Basins in the Northern Suburbs of Chicago IL, 2014 - Justin E. Harbison; Jennifer E. Layden; Christopher Xamplas; Dave Zazra; Marlon Henry; Marilyn O'Hara Ruiz (SAGE Publishing, 2015)
In the northeastern part of the greater Chicago metropolitan area, the North Shore Mosquito Abatement District (NSMAD) treats approximately 50,000 catch basins each season with larvicide tablets as part of its effort to reduce local populations of the West Nile virus (WNV) vector Culex pipiens . During the 2014 season, an NSMAD technician monitored a subset of 60-195 basins weekly for 18 weeks among the communities of the District for the presence of mosquitoes. Monitoring found no clear evidence in the reduction of mosquitoes with the use of larvicides, and visual inspections of 211 larvicide-treated basins found that the majority (162, 76.8%) were missing tablets 1-17 weeks after applications. This loss of treatment may be due to the rapid dissolution or flushing of larvicides and would help explain why the larvicide appeared to be ineffective.